2011
DOI: 10.1155/2011/896896
|View full text |Cite
|
Sign up to set email alerts
|

Blocking Epidermal Growth Factor Receptor Signaling in HTR-8/SVneo First Trimester Trophoblast Cells Results in Dephosphorylation of PKBα/AKT and Induces Apoptosis

Abstract: We identified a major peptide signaling target of EGF/EGFR pathway and explored the consequences of blocking or activating this pathway in the first trimester extravillous trophoblast cells, HTR-8/SVneo. A global analysis of protein phosphorylation was undertaken using novel technology (Kinexus Kinetworks) that utilizes SDS-polyacrylamide minigel electrophoresis and multi-lane immunoblotting to permit specific and semiquantitative detection of multiple phosphoproteins. Forty-seven protein phosphorylation sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…41 Previous studies in HTR-8/SVneo cells demonstrated that EGF triggers STAT5 phosphorylation but does not induce phosphorylation of either STAT1 or STAT3. 7 This study goes in line with our results demonstrating activation of STAT5 but not STAT3 after EGF treatment in HTR8/SVneo and JAR cells. These observations suggest that in trophoblast cells, EGF effects are mediated via STAT5 rather than via STAT3.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…41 Previous studies in HTR-8/SVneo cells demonstrated that EGF triggers STAT5 phosphorylation but does not induce phosphorylation of either STAT1 or STAT3. 7 This study goes in line with our results demonstrating activation of STAT5 but not STAT3 after EGF treatment in HTR8/SVneo and JAR cells. These observations suggest that in trophoblast cells, EGF effects are mediated via STAT5 rather than via STAT3.…”
Section: Discussionsupporting
confidence: 91%
“…Epidermal growth factor can activate STAT1, STAT3, or STAT5 either simultaneously or individually in a cell typedependent manner. 7,37,38 Treatment of EGF results in increase in only p-STAT3 in kidney tubular epithelial cells 39 and only p-STAT5 in U87 glioma cells. 40 In human breast cancer, STAT3 and STAT5 are activated simultaneously by EGF, 38 while in squamous carcinoma cells, EGF activates STAT1 and STAT3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, known pathways (e.g., ErbB and insulin signaling pathways; Table S2) were enriched. We identified 7 key upregulated phosphorylation sites in ErbB signaling pathways, such as T693 in EGFR 28 , Y427 in SHC1 29 , S10 in CDKN1B 30 , Y216 in GSK3B 31 , S241 in PDPK1 32 , and S226 33 and T394 in MAP2K2 34, 35 (Figure 6e). In addition, mRNA splicing was found to be activated after EGF treatment (Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…To test BPS’ EGFR antagonism, HTR-8/SVneo cells were used. HTR-8/SVneo is a first-trimester human extravillous trophoblast cell line with EGFR expression [ 63 ] that proliferates and invade in response to EGF [ 49 ]. HTR-8/SVneo were maintained in basic medium, Dulbecco’s modified Eagle’s medium/F12 medium (Cat#: 124000-024, MilliporeSigma, Saint Louis, MO, USA) supplemented with 10% of fetal bovine serum (FBS), 2 mM L-glutamine, 10 mM HEPES, 100 IU/mL penicillin, and 100 μg/mL streptomycin.…”
Section: Methodsmentioning
confidence: 99%